Techno-economic assessment of polygeneration based on fluidized bed gasification. (15th August 2019) - Heinze, Christian; May, Jan; Peters, Jens; Ströhle, Jochen; Epple, Bernd
Abstract: The electric power sector contributes to about a quarter of the total CO2 emissions worldwide. Therefore, in most mitigation scenarios for the climate change the share of low-carbon electricity supply increases from the current share of approximately 30% to more than 80% by 2050. A promising approach is the polygeneration concept for electrical power and chemicals based on integrated gasification combined cycle. It offers the possibility to capture CO2 in a very efficient pre-combustion process and is able to accommodate the intermittent renewable power generation from wind and solar while operating the gasification island at full load by producing synthetic chemical products during times of low power demand. In this work, a process model of a polygeneration plant including a 350 MWel combined cycle power plant with a fluidized bed dryer, a fluidized bed gasifier, a gas purification unit, a CO-Shift unit, a Rectisol acid gas removal, and a synthesis reactor array is developed. The model is used to investigate the specific CO2 emissions and the process efficiency for different operation modes for power and methanol production. The model offers two options to introduce excess electricity from renewable sources into the process: via hydrogen from electrolysis or via additional drying and heating of the feedstock. The influence on the process efficiency and the economics are assessed.